The Intelligent Mesh any-to-any? seems to be the byword with PLDT IPVPN. - Choi, Walter Ray (PC World Philippines)
BPOs now enjoy a multipoint-to-multipoint (?any-to-any?) networking solution that links them all together via IP. PLDT is the first local telco to offer true end-to-end IP VPN CoS (Class of Service).